The Role of Ferroptosis in Cancer Development and Treatment Response - Lu, Bin; Chen, Xiao Bing; Ying, Mei Dan; He, Qiao Jun; Cao, Ji; Yang, Bo (Frontiers in Pharmacology, 2018)
Ferroptosis is a process driven by accumulated iron-dependent lipid ROS that leads to cell death, which is a distinct regulated-cell death comparing to other cell death. The lethal metabolic imbalance resulted from GSH depletion or inactivation of glutathione peroxidase 4 (GPX4) is the executor of ferroptosis within the cancer cell. Small molecules-induced ferroptosis has a strong inhibition of tumor growth and enhances the sensitivity of chemotherapeutic drugs, especially in the condition of drug resistance. These evidences have highlighted the importance of ferroptosis in cancer therapeutics, but the roles of ferroptosis in tumorigenesis and development remain unclear. This article provides an overview of the mechanisms of ferroptosis, highlights the role of ferroptosis in cancer and discusses strategies for therapeutic modulation.